Geographical CO2 sensitivity of phytoplankton correlates with ocean buffer capacity. (21st June 2018) - Richier, Sophie; Achterberg, Eric P.; Humphreys, Matthew P.; Poulton, Alex J.; Suggett, David J.; Tyrrell, Toby; Moore, Christopher Mark
Abstract: Accumulation of anthropogenic CO2 is significantly altering ocean chemistry. A range of biological impacts resulting from this oceanic CO2 accumulation are emerging, however, the mechanisms responsible for observed differential susceptibility between organisms and across environmental settings remain obscure. A primary consequence of increased oceanic CO2 uptake is a decrease in the carbonate system buffer capacity, which characterizes the system's chemical resilience to changes in CO2, generating the potential for enhanced variability in p CO2 and the concentration of carbonate [ CO 3 2 − ], bicarbonate [ HCO 3 − ], and protons [H + ] in the future ocean. We conducted a meta‐analysis of 17 shipboard manipulation experiments performed across three distinct geographical regions that encompassed a wide range of environmental conditions from European temperate seas to Arctic and Southern oceans. These data demonstrated a correlation between the magnitude of natural phytoplankton community biological responses to short‐term CO2 changes and variability in the local buffer capacity across ocean basin scales. Specifically, short‐term suppression of small phytoplankton (<10 μm) net growth rates were consistently observed under enhanced p CO2 within experiments performed in regions with higher ambient buffer capacity. The results further highlight the relevance of phytoplankton cell size for the impacts of enhanced p CO2 in both the modern and future ocean. Specifically, cell size‐related acclimation and adaptation to regional environmental variability, as characterized by buffer capacity, likely influences interactions between primary producers and carbonate chemistry over a range of spatio‐temporal scales. Abstract : We evidenced a correlation between the magnitude of natural phytoplankton community biological responses to short‐term CO2 changes and variability in the local buffer capacity across ocean basin scales. Specifically, short‐term suppression of small phytoplankton (<10 µm) net growth rates were consistently observed under enhanced p CO2 within experiments performed in regions with higher ambient buffer capacity. The results further highlight the relevance of phytoplankton cell size for the impacts of enhanced p CO2 in both the modern and future ocean.